Nutritional and therapeutic interventions for diabetes and metabolic syndrome - Bagchi, Debasis, 1954-; Nair, Sreejayan (Elsevier/Academic Press, 2012)
Diabetes mellitus affects approximately 20 million people in the US, or nearly 7% of the population. It is expected to increase by 70% within the next 25 years and numerous epidemiologic studies have demonstrated that type 2 diabetes increases the risk of cardiovascular morbidity and mortality. It is estimated to cost over $92 BILLION in health care costs and lost productivity. The increased risk is due to the detrimental vascular effects of prolonged exposure to a hyperglycemic, oxidant rich environment yielding associated cardiovascular risk factors: atherosclerosis, hypertension and clotting abnormalities. Hypertension and dyslipidemia in diabetic patients produces substantial decreases in cardiovascular and micro vascular diseases. Debasis Bagchi and Nair Sreejayan provides an overview of the current epidemic, outlines the consequences of this crisis and lays out strategies to forestall and prevent diabetes, obesity and other intricate issues of metabolic syndrome.